2020
DOI: 10.1007/s42729-019-00170-4
|View full text |Cite
|
Sign up to set email alerts
|

Silicon in Pre-sprouted Sugarcane Seedlings Mitigates the Effects of Water Deficit After Transplanting

Abstract: This study is aimed at assessing whether silicon (Si) can mitigate the effects caused by water stress in pre-sprouted seedlings (PSS) in sugarcane after their transplanting in the soil and what is the best form in the application if via nutrient solution or leaf spraying. The treatments were arranged in a 3 × 3 factorial scheme with silicon supply via nutrient solution (2 mmol L −1), Si via leaf application (3.4 mmol L −1), and without Si (control) and three levels of soil water retention capacity (70%, 50%, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 29 publications
1
36
1
Order By: Relevance
“…4). The hypothesis that can explain this effect is that Si increases the concentration of Fe in leaves, besides the well-known role of Fe in chlorophyll synthesis (Prado 2008). Moreover, the application of Si decreased the MDA content in leaves and in roots and, consequently, the degradation of chlorophyll.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…4). The hypothesis that can explain this effect is that Si increases the concentration of Fe in leaves, besides the well-known role of Fe in chlorophyll synthesis (Prado 2008). Moreover, the application of Si decreased the MDA content in leaves and in roots and, consequently, the degradation of chlorophyll.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, it has been shown that Si could increases The error bar in the figure represents the standard error. Different lowercase letters represent the differences in the means between Fe condition within the same Si treatments and uppercase letters mark the differences among the Si treatments within the same Fe condition, both were calculated using Tukey's test (significant at p ≤ 0.05) antioxidant activity by mitigating the effect of abiotic stress, such as water deficit in sugarcane plants (Teixeira et al 2020) and Fe deficiency in cucumber plants (Bityutskii et al 2014;Pavlovic et al 2013;Gonzalo et al 2013). Furthermore, Si increased chlorophyll content and biomass accumulation by improving the activity of antioxidant enzymes which resulted in a lower accumulation of ROS in young leaves of barley plants (Nikolic et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Si fertilisation increased proline concentrations and/or ant-oxidant enzymes, such as superoxide dismutase (SOD) and ascorbate peroxidise (APX), in both the cultivars under water stress conditions. Recently, Teixeira et al (2020) suggested that application of Si by means of nutrient solution was more efficient compared to leaf spraying in pre-sprouted sugarcane seedlings to mitigate water stress damage imposed after transplanting in a 30% level of soil water retention capacity. However, water-holding capacity of soil is a vital factor which controls the intensity of drought stress in plants.…”
Section: Water Stressmentioning
confidence: 99%
“…Due to improved growth and yield of sugarcane in response to Si fertilisation (Guntzer et al 2012a;Liang et al 2015;Meena et al 2014;Prakash et al 2018;Savant et al 1999), Si fertilisers are regularly applied to sugarcane in Australia, South Africa and northern and southern America (Kingston 2008;Liang et al 2015;Savant et al 1999;Tubana et al 2016). Improved yield in sugarcane is attributed to increased photosynthetic activity (Cheng 1982;Elawad et al 1982), increased tolerance to salinity (Ashraf et al 2010a, b) and water stress (Camargo et al 2019;Oliveira et al 2010, Teixeira et al 2020, mitigating nutrient toxicity (Clements 1965b;Elawad et al 1982;Fox et al 1967) and enhanced defence mechanisms to a wide range of biotic stresses resulting in increased plant resistance and/or tolerance to such stresses (Haynes 2017;Savant et al 1999).…”
Section: Sources and Forms Of Application Of Silicon In Sugarcanementioning
confidence: 99%